Schistocerca neuropeptides – An update. (January 2022) - Ragionieri, Lapo; Verdonck, Rik; Verlinden, Heleen; Marchal, Elisabeth; Vanden Broeck, Jozef; Predel, Reinhard
Graphical abstract: Highlights: The neuropeptidome was studied by genomics, transcriptomics and mass spectrometry. Peptides from 46 out of 67 genes described were identified by mass spectrometry. 11 neuropeptide genes were found with different transcripts. This dataset is the most comprehensive known from locusts to date. Abstract: We compiled a comprehensive list of 67 precursor genes encoding neuropeptides and neuropeptide-like peptides using the Schistocerca gregaria genome and several transcriptome datasets. 11 of these 67 precursor genes have alternative transcripts, bringing the total number of S. gregaria precursors identified in this study to 81. Based on this precursor information, we used different mass spectrometry approaches to identify the putative mature, bioactive peptides processed in the nervous system of S. gregaria . The thereby generated dataset for S. gregaria confirms significant conservation of the entire neuropeptidergic gene set typical of insects and also contains precursors typical of Polyneoptera only. This is in striking contrast to the substantial losses of peptidergic systems in some holometabolous species. The neuropeptidome of S. gregaria, apart from species-specific sequences within the known range of variation, is quite similar to that of Locusta migratoria and even to that of less closely related Polyneoptera. With the S. gregaria peptidomics data presented here, we have thus generated a very useful source of information that could also be relevant for the study of other polyneopteran species.